Carbon Dioxide Insufflation of the Knee in the Treatment of Full-Thickness Chondral Defects With Micronized Human Articular Cartilage - Mirzayan, Raffy (Arthrosc Tech, 2018)
BioCartilage (BC) is dehydrated, minced human hyaline articular cartilage that was developed as an adjunct to microfracture surgery to help stimulate the bone marrow and stem cells to form hyaline-like tissue in full-thickness chondral defects. The minced pieces of BC require a dry environment for application and can easily be disrupted by residual moisture of saline solution in the surrounding tissues. We present a technique of carbon dioxide insufflation during knee arthroscopy as a means of maintaining a dry environment for preparation of the bony bed during BC augmentation of microfracture surgery. This technique is safe and provides more than adequate visualization, as well as a dry environment, to make the arthroscopic application of BC significantly more efficient.